2019
DOI: 10.1111/idh.12385
|View full text |Cite
|
Sign up to set email alerts
|

Are there any solutions for improving the cleft area hygiene in patients with cleft lip and palate? A systematic review

Abstract: Objective Children with cleft lip and palate (CLP) present high incidence of oral health problems, namely those associated with the accumulation of dental plaque. The objective of this systematic review was to verify if there is any solution to improve the hygiene of the cleft area. Materials and methods A structured systematic review was performed based on articles published in several electronic databases: PubMed, Web of Science, Cochrane Library and Scopus in the last 20 years. The MeSH terms used were clef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…All five out of six studies [ 15 , 16 , 18 , 19 , 26 , 37 ], looking at contamination using filter paper recording methods, found a reduction in contamination over distances beyond 60 cm. One study [ 26 ], found a drop in results to 0 relative fluorescein units [ 38 ] per surface area at 2 to 3 m but registered positive contamination beyond this distance.…”
Section: Resultsmentioning
confidence: 99%
“…All five out of six studies [ 15 , 16 , 18 , 19 , 26 , 37 ], looking at contamination using filter paper recording methods, found a reduction in contamination over distances beyond 60 cm. One study [ 26 ], found a drop in results to 0 relative fluorescein units [ 38 ] per surface area at 2 to 3 m but registered positive contamination beyond this distance.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review in 2019 [18] conducted on scientific articles of the last 20 years examined oral health problems related to the prevalence of caries and to oral hygiene patterns in patients with CLP. The 39 selected articles exhibited a high heterogeneity of type of study, observed population, evaluation periods, and considered variables.…”
Section: Cleft Lip and Palate-related Orodental Issues In The Pediatric Agementioning
confidence: 99%
“…Theme 2: Care Planning Owens, Mistry and Dyer 13 identified a role for the dental team in reviewing the Health Action Plan 19 for a person with a learning disability, where medications which may impact oral health for example, can be identified. 20 Shield et al 21 introduced Dental Passports to accompany Hospital Passports 1 across an NHS Trust area. Bhagat et al 22 and Morley and Lotto 23 researched the efficacy of incorporating oral care education into undergraduate nurse education.…”
Section: Theme 1b: Information Sharing (Training)mentioning
confidence: 99%